Cardiovascular complications of mild autonomous cortisol secretion. Issue 2 (March 2021) - Aresta, Carmen; Favero, Vittoria; Morelli, Valentina; Giovanelli, Luca; Parazzoli, Chiara; Falchetti, Alberto; Pugliese, Flavia; Gennari, Luigi; Vescini, Fabio; Salcuni, Antonio; Scillitani, Alfredo; Persani, Luca; et al.
Abstract : Adrenal incidentalomas (AI) may be associated with a mild autonomous cortisol secretion (MACS) in up to one third of cases. There is growing evidence that MACS patients actually present increased risk of cardiovascular disease and higher mortality rate, driven by increased prevalence of known cardiovascular risk factors, as well as accelerated cardiovascular remodelling. Adrenalectomy seems to have cardiometabolic beneficial effects in MACS patients but their management is still a debated topic due to the lack of high-quality studies. Several studies suggested that so called "non-functioning" AI may be actually "functioning" with an associated increased cardiovascular risk. Although the individual cortisol sensitivity and peripheral activation have been recently suggested to play a role in influencing the cardiovascular risk even in apparently eucortisolemic patients, to date the degree of cortisol secretion, as mirrored by the cortisol levels after dexamethasone suppression test remains the best predictor of an increased cardiovascular risk in AI patients. However, whether or not the currently used cut-off set at 50 nmol/L for cortisol levels after dexamethasone suppression could be considered completely reliable in ruling out hypercortisolism remains unclear.